Combined surface micropatterning and reactive chemistry maximizes tissue adhesion with minimal inflammation - Pereira, Maria J. N. (2013)
The use of tissue adhesives for internal clinical applications is limited due to a lack of materials that balance strong adhesion with biocompatibility. The use of substrate topography was explored to reduce the volume of a highly reactive and toxic glue without compromising adhesive strength. Micro-textured patches coated with a thin layer of cyanoacrylate glue achieved similar adhesion levels to patches employing large amounts of adhesive, and was superior to the level of adhesion achieved when a thin coating was applied to a non-textured patch. In vivo studies demonstrated reduced tissue inflammation and necrosis for patterned patches with a thinly coated layer of reactive glue, thus overcoming a significant challenge with existing tissue adhesives such as cyanoacrylate. Closure of surgical stomach and colon defects in a rat model was achieved without abdominal adhesions. Harnessing the synergy between surface topography and reactive chemistry enables controlled tissue adhesion with an improved biocompatibility profile without requiring changes in the chemical composition of reactive tissue glues.